Notary's Responsibility for Making a Deed of Statement of Meeting Decisions Based on Circular Meeting Decisions as a Substitute for the General Meeting of Shareholders (GMS) - Naim, Muhammad (Program Studi Master of Notary Law (S2), Faculty of Law, Universitas Islam SUltan Agung, 2024)
This study aims to find out and analyze the notary's responsibility for making a deed of statement of meeting decisions based on circular meeting decisions as a substitute for a general meeting of shareholders (GMS) and to find out and analyze the position of the deed of notary made in connection with the existence of a lawsuit for unlawful acts resulting from the Deed of Statement of Meeting Decisions Based on Circular Meeting Decisions as a Substitute for the General Meeting of Shareholders (GMS).This study uses a normative legal library research method and from the results of the author's research, there are several problems that arise due to the making of a deed of amendment to the articles of association by a notary based on a circular decision. The results of the study show that notariesnot responsible for all kinds of substantial truth of the statements of the parties contained in the circular decision deed and the deed made because the existence of a lawsuit for an unlawful act does not automatically make it null and void by law if the elements of an unlawful act are not fulfilled.